"Biodegradable House" – designing in a way that is compatible with nature as a challenge for an architect - Kocki, Wojciech; Kasprzycka, Karolina (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
The purpose of this article is to show the possibility of using selected materials of natural origin in single-family housing. The impulse to carry out study design work is the increase in global carbon dioxide emissions, in which the construction sector plays an important role. The solution to reduce greenhouse gas emissions is the use of biodegradable materials, among which we can distinguish a hemp-lime composite. Thanks to its practical features, hemp is widely used in various industries, including architecture. In the engineering diploma thesis, special attention was paid to the possibility of using hemp composite in the designed architectural elements. The assumption was made to minimize materials with unfavorable properties and a large carbon footprint, thus reducing energy consumption and the negative impact of residential buildings on the environment.